Effective Management of Information as Empowerment Tools in Opressed System: A Lesson for Muslim Farmers in Kano State - Atah, Ummi Ibrahim; Abideen, Adewale; Umar, Mustapha; Galadanchi, Aisha Aliyyu (International Conference of Moslem Society, 2018)
Effective management of information is a systematic design of generation, control and transmission of information in a close or open inter-related system for the attainment of the system’s goals. As a powerful tool that has been utilized to win lost battles for centuries, control of information have been the winning bait of leaders against their followers in many underdeveloped worlds. Little input on information sharing and networking of vulnerable group as seen in text message programme of Kenya’s farmers have shown astronomical improvement of farmers life and economy. Hinging on the backdrop of this concept, this study conducted a preliminary interview with Kano state farmers to assess their level of contact with the government and financial related agencies. The study revealed a wide communication gap between the farmers and government programmes and Corruption has been identified as the major problem. Using simple but modern means of communication, we design and propose a root-to-top communication programme for effective networking of information management with the view of circumventing the corruption-ridden conventional means of communication. Three communication stages of the proposed programme includes; the enlightenment, implementation and feedback mechanism. Therefore, cluster communication is identified as one of the key to success of bridging communication gap between government and other financial related agencies with farmers. It is therefore recommended that site specific features be considered before application of any cluster communication system for effective service delivery.